2021
DOI: 10.1002/jia2.25843
|View full text |Cite
|
Sign up to set email alerts
|

Experiences, perceptions and potential impact of community‐based mentor mothers supporting pregnant and postpartum women with HIV in Kenya: a mixed‐methods study

Abstract: IntroductionCommunity‐based mentor mothers (cMMs) are women living with HIV who provide peer support to pregnant/postpartum women living with HIV (PWLWH) to enhance antiretroviral therapy (ART) adherence, retention in care and prevent perinatal transmission of HIV. The goal of this study was to explore the experiences, perceptions, mechanisms and health impact of cMMs on PWLWH in Kenya from the perspective of cMMs.MethodsWe conducted a prospective mixed‐methods study in southwestern Kenya in 2015–2018. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This offers clear indicators about material amounts, available studies, and general descriptions (wide or comprehensive) (Tricco et al, 2018). This research, which focuses on the involvement of fathers in breastfeeding, follows the guidelines established by the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) framework for scoping review (PRISMA-ScR) (Helova et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This offers clear indicators about material amounts, available studies, and general descriptions (wide or comprehensive) (Tricco et al, 2018). This research, which focuses on the involvement of fathers in breastfeeding, follows the guidelines established by the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) framework for scoping review (PRISMA-ScR) (Helova et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in other resource-limited settings have shown better PMTCT intervention adherence with the use of community-based counseling, support groups, and home visits [17][18][19][20]. Additionally, studies in Kenya have demonstrated that peer support from community-based mentor mothers to improve ART adherence and retention in care was well accepted among women living with HIV [21,22].…”
Section: Introductionmentioning
confidence: 99%
“… 7 They have also successfully contributed to improving treatment outcomes in adolescents and young people living with HIV by increasing access to care and improving treatment adherence. 10 , 11 As community cadres deliver services to their peers, they may be neglected since healthcare providers are likely to unintentionally think that the cadres should know better about HIV and require little or no support due to their work in supporting their peers. Yet, it is unclear if community cadres’ additional role in supporting their peers affects their QoL.…”
Section: Introductionmentioning
confidence: 99%